Memahami Problema Kebijakan Telemanika - Ana Nadhya Abrar (Magister Administrasi Publik, 2002)
The art changing and development of the information technologies, mainly Internet, have to be responded quickly by Indonesian government bypreparing a set of new policies to reduce its negative impacts. This idea is driven by the fact that many problems experienced by the Internet users, so far, cannot be solved by the laws and regulations which already existed before i.e. LawNo 36/1999 andNo. 9/ 1999. Therefore, the author suggests in this article that more pressures and intensive political lobby are needed to convince the DPR that it is very urgent to take immediate action i.e. to discuss the Tekmatika bill and then legalize it to become the law.